Efficacy and safety of 0.1% kinetin cream in the treatment of photoaging skin - Rungsima Wanitphakdeedecha (2018)
© 2015 Indian Journal of Dermatology, Venereology, and Leprology. Background: Kinetin is a plant-derived compound, which is reported to possess antiaging properties. It has been used in a topical cream to manage facial photo-damage and aging. Although studies elsewhere have shown its benefits, not many studies of the effects of kinetin in Asian skin are available. Objectives: To assess the efficacy and tolerability of 0.1% kinetin cream in the treatment of facial photo-aging. Methods: The study was designed to be open-label and single-blinded, without a control group. One hundred Thai female and male subjects with mild, moderate or severe facial photo-damage were enrolled. They were asked to apply 0.1% kinetin cream twice daily for 12 weeks and follow up at 4, 8, and 12 weeks. Subjective patient self-assessment and physician assessment of facial skin photo-damage were accompanied by digital photographic analysis using the VISIA® (Canfield Scientific Inc, Fairfield, NJ) imaging system. Results: At baseline, most patients reported moderate skin changes related to photo-damage, skin texture, skin color and wrinkles. After 12 weeks, physician and patient assessments showed slight but statistically significant improvements in overall skin condition, skin texture, color, and wrinkles. Findings were similar with the digital photographic system analysis, especially in relation to skin color. Facial ultraviolet spots and redness also showed statistically significant improvements after 12 weeks. The treatment was generally well tolerated. Limitations: The study was designed to be pragmatic and hence no randomization was carried out; there were also no intrapatient or interpatient control observations, and no comparison arm. Conclusion: Kinetin (0.1%) cream was found to slightly improve cutaneous facial photo-damage after 12 weeks of use in a group of Thai patients.